2022
DOI: 10.1126/science.abc4916
|View full text |Cite
|
Sign up to set email alerts
|

Predator control of marine communities increases with temperature across 115 degrees of latitude

Abstract: Early naturalists suggested that predation intensity increases toward the tropics, affecting fundamental ecological and evolutionary processes by latitude, but empirical support is still limited. Several studies have measured consumption rates across latitude at large scales, with variable results. Moreover, how predation affects prey community composition at such geographic scales remains unknown. Using standardized experiments that spanned 115° of latitude, at 36 nearshore sites along both coasts of the Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 39 publications
(86 reference statements)
1
30
0
Order By: Relevance
“…However, one study found that horseshoe crab prey was most abundant in northern sites that did not align with where the largest horseshoe crabs are found (Smith, 2012). Predation pressure on benthic invertebrates is often shown to increase with temperature (Ashton et al, 2022; Duffy et al, 2015; Fawcett, 1984; Heck & Wilson, 1987) and there is evidence of relationships between body size and predation pressure in invertebrates (Blumenshine et al, 2000; Quintana et al, 2015; Detmer et al, 2017). For example, decreased predation by starfish in the colder portion of the range was hypothesized to contribute to an increasing body size cline in the marine gastropod Tegula atra (Palacios Subiabre et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, one study found that horseshoe crab prey was most abundant in northern sites that did not align with where the largest horseshoe crabs are found (Smith, 2012). Predation pressure on benthic invertebrates is often shown to increase with temperature (Ashton et al, 2022; Duffy et al, 2015; Fawcett, 1984; Heck & Wilson, 1987) and there is evidence of relationships between body size and predation pressure in invertebrates (Blumenshine et al, 2000; Quintana et al, 2015; Detmer et al, 2017). For example, decreased predation by starfish in the colder portion of the range was hypothesized to contribute to an increasing body size cline in the marine gastropod Tegula atra (Palacios Subiabre et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Using the latest global database of living brachiopods recently established by Ye et al (2021), this paper sought to provide a novel study of how the surface ornament of living brachiopod shells varies with latitude and bathymetry. In particular, the study aimed to test the hypothesis that the strength of shell ornament, as a proxy for an anti-predatory defense mechanism against predation, decreases with latitude and water depth (Ashton et al, 2022;Freestone et al, 2021;Oji, 1996;Reynolds et al, 2018).…”
Section: Four Typesmentioning
confidence: 99%
“…Using the latest global database of living brachiopods recently established by Ye et al (2021), this paper sought to provide a novel study of how the surface ornament of living brachiopod shells varies with latitude and bathymetry. In particular, the study aimed to test the hypothesis that the strength of shell ornament, as a proxy for an anti‐predatory defense mechanism against predation, decreases with latitude and water depth (Ashton et al, 2022; Freestone et al, 2021; Harper & Peck, 2016; Oji, 1996; Reynolds et al, 2018). In other words, if the scenario that intense predation pressure usually occurs in low latitudes and shallow water areas holds, we then should expect to see an increase of more brachiopods with ornamentation, and more complicated or stronger ornamentation to be more frequently associated with brachiopods living in lower latitude or shallower water habitats (or habitats near the continental shelf).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, artificial coastal structures typically support sessile assemblages distinct from natural systems (Bulleri & Chapman, 2010). Nonetheless, artificial structures have been extensively and successfully used to evaluate ecological dynamics of sessile communities across latitudinal gradients (Ashton et al, 2022; Freestone et al, 2021; Freestone & Osman, 2011). Beyond sessile communities, dock pilings also support abundant fish communities, which, on account of the widespread prevalence of docks, may provide an additional useful, standardized system for large‐scale, manipulative studies (Brandl et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, artificial coastal structures typically support sessile assemblages distinct from natural systems (Bulleri & Chapman, 2010). Nonetheless, artificial structures have been extensively and successfully used to evaluate ecological dynamics of sessile communities across latitudinal gradients (Ashton et al, 2022;Freestone et al, 2021;Freestone & Osman, 2011).…”
Section: Introductionmentioning
confidence: 99%